Food Insecurity Associated with Double-Burden of Malnutrition among Women in Reproductive Age in Ciampea Sub-district, Bogor, West Java - Seala Septiani; Ismi Irfiyanti; Tran Thi Hai; Helda Khusun; Luh Ade Wiradnyani; Aria Kekalih; Paulus Daniel Sahanggamu (Indonesian Journal of Public Health Nutrition, 2021)
AbstractDouble burdens of malnutrition among women have occurred across most developing countries including Indonesia. This study compared the associated factors among overweight and underweight of women in reproductive age (WRA) in rural Ciampea Sub-district, Bogor, West Java. This cross-sectional study surveyed the nutritional status of 575 mothers (16-49 years old) who have under two-years-old children. Nutritional status was assessed by body-mass-index (BMI) and mid-upper arm circumference (MUAC), food security status by US-Food Security Survey Module (US-FSSM), dietary intake by a single 24-H dietary recall. The prevalence of underweight, overweight, and obese among this group were 10%, 15.8%, and 34.2%. Food security status was the single factor associated with overweight (p=0.026). However, after adjustment with other factors, food insecurity with hunger was found to be the highest risk of being underweight (AdjOR=3.95; 95%CI: 1.46-10.64). Contrarily, it contributed to lower chances of being overweight among WRA (AdjOR=0.40, 95%CI: 0.21-0.77). In conclusion, food security status in this population associated with both under- and over-nutrition, in addition to other factors such as age and education level of WRA. Ensuring the availability and affordability of nutritious food together with proper nutrition education to rural communities might be worthwhile to improve this condition.AbstrakBeban ganda malnutrisi pada wanita terjadi di sebagian besar negara berkembang, termasuk Indonesia. Penelitian ini membandingkan faktor-faktor yang berhubungan pada wanita usia subur (WUS) dengan status gizi kurang dan lebih di pedesaan Ciampea, Bogor, Jawa Barat. Studi potong lintang ini mensurvei status gizi pada 575 Ibu (usia 16-49 tahun) yang memiliki baduta. Penilaian status gizi menggunakan indeks massa tubuh (IMT) dan lingkar lengan atas (LILA), status ketahanan pangan oleh US-Food Security Survey Module (US-FSSM), asupan makanan dengan food recall 24-jam. Prevalensi gizi kurang, lebih, dan obesitas pada kelompok ini adalah 10%, 15,8%, dan 34,2%. Status ketahanan pangan merupakan faktor tunggal yang terkait dengan kelebihan berat badan (p = 0,026). Namun, setelah disesuaikan dengan faktor lain, kerawanan pangan dengan kelaparan ditemukan sebagai risiko tertinggi terjadinya gizi kurang (AdjOR = 3.95; CI 95%: 1.46-10.64). Sebaliknya, kondisi tersebut berisiko lebih rendah terhadap kejadian gizi lebih pada WUS (AdjOR = 0,40, 95% CI: 0,21-0,77). Kesimpulannya, status ketahanan pangan pada populasi ini berhubungan dengan kejadian ganda malnutrisi, selain faktor lain seperti usia dan tingkat pendidikan. Memastikan ketersediaan dan keterjangkauan pangan bergizi bersama dengan edukasi gizi yang tepat untuk masyarakat pedesaan mungkin bermanfaat untuk memperbaiki kondisi ini.